Research on the Characteristics of Microscopic Damage to Different Pore Types by Slippery Water Fracturing Fluid in the Chang Member Tight Sandstone Reservoir, Ordos Basin, NW China. (6th January 2021) - Qi, Aojiang; Qian, Pinshu; Huang, Hai; Ren, Dazhong; Gu, Xiaoyu; Zhang, Fan; Yuan, Xun
Abstract : This paper examines the damage caused by slickwater fracturing fluid to the microscopic pore structure of tight sandstone in the Chang 7 member in the Ordos Basin. A submicron CT in situ displacement system was used to analyze and graphically represent changes in pores in core samples following fracturing fluid damage. The results show the following: (1) the damage caused by slickwater fracturing fluid to tight sandstone fractures mainly occurs in the early stage of fluid incursion. The damage is characterized by a decrease in the effective pore volume, increase in the number of pores, and insignificant subsequent damage. The main causes of pore damage by slickwater fracturing fluid are retention of slickwater in the liquid phase and hydration swelling of clay minerals in the pores. (2) After the high pressure intrusion of slickwater fluid, the pore size of large-size intergranular pores increases, and there is no obvious damage after water flooding. However, fractures and small dissolution pores in the cores are the main areas of fluid retention after fracturing fluid invasion due to their small flowing radius and complex structure. These are the locations where damage mostly occurs.